2011
DOI: 10.1515/ijamh.2011.008
|View full text |Cite
|
Sign up to set email alerts
|

Level of training of nursing staff and the autonomy given to psychiatric inpatients: a multicenter study

Abstract: This research examines the infl uence of the level of professional training of the caretaking staff in psychiatric wards, the type of wards in which a patient is treated and the patient ' s age compared with the level of limitation put on patient autonomy. Detailed questionnaires were administered to 296 nurses from fi ve mental health centers who met inclusion criteria for the study. The level of autonomy restriction was measured using six representative cases from fi eldwork of the interviewees. These cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In a Swedish study, it was found that nursing assistants supported the older persons' preferences to a higher extent than nurses' aides (Mattiasson & Andersson 1995). This is in conformity with results showing that the level of professional training predicts the extent of autonomy given to the patients (Leibovich et al 2011).…”
Section: Introductionsupporting
confidence: 63%
“…In a Swedish study, it was found that nursing assistants supported the older persons' preferences to a higher extent than nurses' aides (Mattiasson & Andersson 1995). This is in conformity with results showing that the level of professional training predicts the extent of autonomy given to the patients (Leibovich et al 2011).…”
Section: Introductionsupporting
confidence: 63%